Uso excesivo de fármacos y su relación con complicaciones, en insuficiencia respiratoria aguda, en niños menores de 2 años. Subcentro de la Parroquia San Juan de Puebloviejo periodo octubre 2019 - marzo 2020 - García Huacon, Genesis Maritza (2020)
The development of this work focused on excessive drug use and its relationship with complications, in acute respiratory failure, in children under 2 years of age, sub-center of the parish San Juan de Puebloviejo, for which it was established as a general objective to determine the Relationship between excessive drug use and complications in acute respiratory failure in children under 2 years of age, which leads to determining what relationship the mother's knowledge has about the excessive use of drugs with complications in children in children of 2 years with acute respiratory insufficiencies, the complications presented in children under 2 years were identified and action measures were proposed to provide adequate information to prevent acute respiratory insufficiencies. The theoretical framework of the work was based on the variables of the research. Regarding the methodology, a quantitative and qualitative approach was required, to know the background, complications of excessive drug use in acute respiratory insufficiencies in children under 2 years of age, to demonstrate the causes they present, the technique applied was the survey, which was addressed to the mothers of children under 2 years. The results obtained made it possible to clarify the assumptions and to determine that indeed the excessive use of the drug affects acute respiratory insufficiencies, due to the lack of knowledge that mothers have about these respiratory diseases, therefore, Educational workshops on the excessive use of drugs and its influence on complications in acute respiratory failure in children under 2 years.